Exploring alternatives to scale FTT-SE to large networks - Farahnaz Yekeh (2011)
Nowadays, most complex embedded systems follow a distributed approach in which a network interconnects potentially large numbers of nodes. One technology that is being increasingly used is switched Ethernet, but real-time variants of this protocol typically limit scalability. In this paper, we focus on the scalability of the Flexible Time Triggered communication over Switched Ethernet (FTT-SE), which has been proposed to support hard real-time applications in a flexible and predictable manner. Moreover, time-triggered and event-triggered communication methods are supported in this protocol. FTT-SE has already been explored and investigated for small scale networked applications. In this paper we address the protocol scalability and suggest three different solutions with a qualitative assessment. Â(c) 2011 IEEE.